Daniel Tiger's neighborhood. Daniel's winter wonderland [videorecording (DVD)]. (PBS Distribution, 2016)
It's a snowy day in the Neighborhood, and Daniel Tiger can't wait to play outside. Miss Elaina comes over to Daniel's house. Before they can go outside, Daniel learns that playtime in the snow is only grr-ific when he wears clothes that will keep him warm. Daniel also discovers that when an activity such as sledding or ice skating seems scary and hard to do, he can try a little bit at a time and then it's easier.